Long-term surrogate cardiovascular outcomes of SGLT2 inhibitor empagliflozin in chronic heart failure: a systematic review and meta-analysis - Qingkai Yan; Xinrao Chen; Changqing Yu; Yuehui Yin (BMC Cardiovascular Disorders)
Abstract The sodium‒glucose cotransporter-2 (SGLT2) inhibitor empagliflozin (EMPA) has been demonstrated to reduce the risk of cardiovascular mortality or hospitalization for heart failure (HF) in patients. Nevertheless, data concerning the long-term cardiovascular effects in clinically important subgroups are scarce. A prespecified meta-analysis of randomized controlled trials (RCTs) was conducted to assess the long-term effects of EMPA on cardiovascular outcomes in HF patients, regardless of HF type and glycemic status. The assessment included parameters related to left ventricular (LV) remodeling, including the LV volume, the LV mass index (LVMI), the ejection fraction, the systolic blood pressure, and biomarkers. Moreover, the effects of the treatment on exercise capacity and quality of life (QoL) were analyzed. Furthermore, these cardiovascular parameters were evaluated in prespecified subgroups of HF patients, including type of HF, type 2 diabetes status, and duration of therapy. The quantitative meta-analysis was synthesized and analyzed via the statistical software Stata 17.0. The meta-analysis revealed that EMPA administration significantly contributed to a reduction in systolic blood pressure (SBP) (MD = 4.93 mmHg, 95% CI=[-9.67, -0.19]; P < 0.0001) and left ventricular end-diastolic volume (LVEDV) (MD=-18.03 mL, 95% CI=[-25.4, -10.67], P < 0.0001). Furthermore, left ventricular end-systolic volume (LVESV) (MD=-16.09 mL, 95% CI=[-26.94, -5.25]; P < 0.0001) and N-terminal pro-B-type NP (NT-proBNP) (SMD=-0.54, 95% CI=[-0.94, -0.13]; P = 0.01) significantly decreased. These decreases were accompanied by improvements in the 6-minute walk distance (6MWD, SMD = 0.78, 95% CI=[-0.22, -1.79], P = 0.13) and KCCQ score (MD = 1.98, 0.97–2.99; P < 0.0001). The results of the subgroup analysis indicated that EMPA administration was associated with more pronounced benefits in terms of cardiac remodeling, function and exercise capacity for specific populations, including (1) HF with a reduced ejection fraction (HFrEF); (2) the absence of diabetes; and (3) treatment for no less than 6 months. Additionally, EMPA may lead to an increased risk of cardiovascular adverse events (AEs) but is less effective for improving the QoL in HF patients with preserved EF (HFpEF) populations.